2010
DOI: 10.1097/mat.0b013e3181d7db0c
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanical Simulator of Cardiac Wall Kinematics

Abstract: Aim of this study is to develop a mechanical simulator (MS) reproducing cardiac wall kinematics [i.e., radial (R), longitudinal (L) and rotational (RT) motions] to test piezoelectric gyroscopic sensors (GS) that are able to measure cardiac torsion that has proved to be a sensitive index of cardiac performance. The MS consists of three brushless motors controlled by a dedicated software either separately or simultaneously reproducing the three main cardiac wall movements (R, L, RT) obtained by implementing diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…1 ). The two processes may not be affected in the same way by ventricular dysfunction [ 29 ], so their evaluation may represent a valuable tool for clinical practice, even in moderate pathological situations that are not detected by analysing classical hemodynamic parameters [ 17 , 26 , 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). The two processes may not be affected in the same way by ventricular dysfunction [ 29 ], so their evaluation may represent a valuable tool for clinical practice, even in moderate pathological situations that are not detected by analysing classical hemodynamic parameters [ 17 , 26 , 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we reported preliminary in vitro evaluations of the new implantable CardioMon lead, tested using a mechanical simulator of cardiac rotational movements. Additional lab tests will be conducted using an upgraded mechanical simulator that we recently designed, which is capable of reproducing all three components of cardiac motion (longitudinal, radial, and rotational) combined into synchronous movements [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pathologies which affect the fibers architecture and cardiac geometry were proved to alter the cardiac torsion pattern. For these reasons, the cardiac torsion represents a sensitive index of ventricular performance [9], [10], [11], [12], [13]. The assessment of cardiac torsion as a sensitive clinical index has led to a substantial increase of the number of experimental and clinical studies aimed at quantifying this parameter.…”
Section: Introductionmentioning
confidence: 99%